Neuronal Migration Generates New Populations of Neurons That Develop Unique Connections, Physiological Properties and Pathologies - Fritzsch, Bernd; Elliott, Karen L.; Pavlinkova, Gabriela; Duncan, Jeremy S.; Hansen, Marlan R.; Kersigo, Jennifer M. (Frontiers in Cell and Developmental Biology, 2019)
Central nervous system neurons become postmitotic when radial glia cells divide to form neuroblasts. Neuroblasts may migrate away from the ventricle radially along glia fibers, in various directions or even across the midline. We present four cases of unusual migration that are variably connected to either pathology or formation of new populations of neurons with new connectivities. One of the best-known cases of radial migration involves granule cells that migrate from the external granule cell layer along radial Bergman glia fibers to become mature internal granule cells. In various medulloblastoma cases this migration does not occur and transforms the external granule cell layer into a rapidly growing tumor. Among the ocular motor neurons is one unique population that undergoes a contralateral migration and uniquely innervates the superior rectus and levator palpebrae muscles. In humans, a mutation of a single gene ubiquitously expressed in all cells, induces innervation defects only in this unique motor neuron population, leading to inability to elevate eyes or upper eyelids. One of the best-known cases for longitudinal migration is the facial branchial motor (FBM) neurons and the overlapping inner ear efferent population. We describe here molecular cues that are needed for the caudal migration of FBM to segregate these motor neurons from the differently migrating inner ear efferent population. Finally, we describe unusual migration of inner ear spiral ganglion neurons that result in aberrant connections with disruption of frequency presentation. Combined, these data identify unique migratory properties of various neuronal populations that allow them to adopt new connections but also sets them up for unique pathologies.